Nanocarriers for organ-specific and localised drug delivery - Shah, Muhammad Raza (Micro and nano technologies, 2022)
Organ-specific drug delivery is aimed at achieving increased concentration of therapeutic molecules at target sites with minimum side effects on other healthy tissues. Similarly, drug-specific delivery to some vital organs, such as the brain, lungs, heart and kidneys remains a challenging task for the formulation scientists. Oral delivery of most of the commercially available life-saving drugs has also been impeded by various physio-chemical and biological barriers. These advancements in nanotechnology have led to the development of various pharmaceutical nanocarriers. Nanocarriers for Organ-Specific and Localized Drug Delivery summarizes targeted drug delivery systems and approaches to the major organs of the body. The book shows how drugs can be specifically targeted to the pathological area within an organ in a viable way. Employing pharmaceutical nanocarriers for drug delivery targeted to specific organs of the body requires a comprehensive knowledge of the disease site's pathophysiology as well as physical, chemical and pharmaceutical techniques for modification or functionalization of the nanocarriers. Combining theoretical principles and practical applications of various nanocarriers for organ-specific drug delivery, this is an important reference source for all those seeking to increase their understanding of how pharmaceutical nanocarriers are being used to create more efficient drug delivery systems.